2018
DOI: 10.18671/scifor.v46n119.07
|View full text |Cite
|
Sign up to set email alerts
|

Análise dialélica na avaliação do potencial de híbridos de Pinus elliottii x Pinus caribaea para a formação de populações de melhoramento

Abstract: Uma das dificuldades no melhoramento florestal é o longo ciclo de seleção de materiais genéticos superiores em qualidade e produtividade, problema que pode ser contornado via seleção precoce de híbridos. O objetivo da presente pesquisa foi estimar os parâmetros genéticos para caracteres silviculturais e verificar a viabilidade da seleção precoce em híbrido de Pinus elliottii x Pinus caribaea, visando a formar uma população base de melhoramento. O experimento foi estabelecido em delineamento em blocos ao acaso,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
4
1
0
Order By: Relevance
“…According to the classification of Resende (2002), heritabilities below 0.15 were classified as low magnitude, heritabilities between 0.15 and 0.50 are classified as intermediate magnitude, and heritabilities above 0.50 are classified as high magnitude. The heritabilities observed were similar to those obtained by Tambarussi et al (2010), Souza et al (2017) and Tambarussi et al (2018) and are higher than those reported by Silva et al (2011).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…According to the classification of Resende (2002), heritabilities below 0.15 were classified as low magnitude, heritabilities between 0.15 and 0.50 are classified as intermediate magnitude, and heritabilities above 0.50 are classified as high magnitude. The heritabilities observed were similar to those obtained by Tambarussi et al (2010), Souza et al (2017) and Tambarussi et al (2018) and are higher than those reported by Silva et al (2011).…”
Section: Discussionsupporting
confidence: 89%
“…The progenies of Pinus caribaea var. hondurensis had results similar to those reported by Durigan et al (2004) in Assis, São Paulo, at three years after planting; by Donadoni et al (2010) in Vilhena, Rondônia, at three years of age and by Tambarussi et al (2018) in Canoinhas, Santa Catarina, at four years after planting. The latter observed an average of 5 cm DBH, 4 m H and 1.63 m² plant -1 CPA, which demonstrates the potential of the tested progenies for the region of Lavras.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations